From an Alternative Medicine to a New Treatment for Refractory Epilepsies: Can Cannabidiol Follow the Same Path to Treat Neuropsychiatric Disorders? - Bitencourt, Rafael M.; Takahashi, Reinaldo N.; Carlini, Elisaldo A. (Frontiers in Psychiatry, 2021)
Although cannabis has been known for ages as an “alternative medicine” to provide relief from seizures, pain, anxiety, and inflammation, there had always been a limited scientific review to prove and establish its use in clinics. Early studies carried out by Carlini’s group in Brazil suggested that cannabidiol (CBD), a non-psychotropic phytocannabinoid present in Cannabis sativa, has anticonvulsant properties in animal models and reduced seizure frequency in limited human trials. Over the past few years, the potential use of cannabis extract in refractory epilepsy, including childhood epilepsies such as Dravet’s syndrome and Lennox-Gastaut Syndrome, has opened a new era of treating epileptic patients. Thus, a considerable number of preclinical and clinical studies have provided strong evidence that phytocannabinoids has anticonvulsant properties, as well as being promising in the treatment of different neuropsychiatric disorders, such as depression, anxiety, post-traumatic stress disorder (PTSD), addiction, neurodegenerative disorders and autism spectrum disorder (ASD). Given the advances of cannabinoids, especially CBD, in the treatment of epilepsy, would the same expectation regarding the treatment of other neuropsychiatric disorders be possible? The present review highlights some contributions from Brazilian researchers and other studies reported elsewhere on the history, preclinical and clinical data underlying the use of cannabinoids for the already widespread treatment of refractory epilepsies and the possibility of use in the treatment of some neuropsychiatric disorders.